(3HdGO GdYQH hLHGdgG hejGggG hChOjJgGs - (3GdMSf Hf eMeO GdCUHgGfj, CHh Ydj GdeYQha HdZOI, Ch dZPI Ch dcPI, hdYdg HGdcGa GdeYbhOI,J (B311 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3bGd GHh Ydi dZOI GdCUagGfi ef ejGg Hfi Ybjd HfLO s
(3BNQgG (B:s
(3hYjhf GdGQJbGA CjVkG gVHI dHfi cdGH s
(3HgG fXGe GdJYbjHIs
(3fSNJ gPg GdfSNI ef fSNI cKjQI GdZdW hGdJMQja hGdSbWs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B238s
Keywords: (3GdLZQGajG h GdHdOGfs